IMPROVING STUDENTS' LEARNING OUTCOMES AND LEARNING MOTIVATION IN LIGHT MATERIAL THROUGH A CULTURALLY RESPONSIVE TEACHING APPROACH - Moch. Bachrul Ulum; Elsa Munawarotul Jannah; Dwi Amiliatuz Zaqiyah; Maryani (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari, 2026)
This study aims to improve students' motivation and learning outcomes in science subjects of class VIIIA at SMPN 3 Jember through the application of the Culturally Responsive Teaching (CRT) approach. This study used a Classroom Action Research (CAR) method with two cycles. The results showed that the application of the CRT approach was effective in improving students' motivation and learning outcomes. Students' learning outcomes in cycle I increased from an average post-test score of 85.45 to 89.39 in the average post-test score of cycle II. Students' learning completeness also experienced a significant increase. In cycle I, 4 students (12.12%) were declared to have completed the pre-test, while in the post-test it increased to 30 students (90.91%). In cycle II, 5 students (15.15%) were declared to have completed the pre-test, and increased to 31 students (93.94%) were declared to have completed the post-test. The CRT approach has been proven effective in improving students' motivation and learning outcomes in science subjects. Keywords: Culturally Responsive Teaching (CRT), learning outcomes, and learning motivation.